Crisis and Prosperity in Sung China, editado por John Winthrop Haeger. (Tucson: University of Arizona Press, 1975), pp. xv, 264. - Chan, Ming K.; González-Richmond, Carlos D. (Estudios de Asia y África, 1976)
-